2009
DOI: 10.1063/1.3263604
|View full text |Cite
|
Sign up to set email alerts
|

Accurate dipole polarizabilities for water clusters n=2–12 at the coupled-cluster level of theory and benchmarking of various density functionals

Abstract: The static dipole polarizabilities of water clusters (2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 115 publications
3
83
0
Order By: Relevance
“…As concluded by Hammond et al 8 for water clusters at various coupled-cluster levels of theory, triple or higher excitations are less significant as the number of molecules increases. Noteworthy, the calculation of amino acid aggregates is currently very challenging at the CCSDT level of theory even with the smaller aug-cc-pVDZ basis set.…”
Section: Electron Correlation and Basis Set Effectsmentioning
confidence: 79%
See 1 more Smart Citation
“…As concluded by Hammond et al 8 for water clusters at various coupled-cluster levels of theory, triple or higher excitations are less significant as the number of molecules increases. Noteworthy, the calculation of amino acid aggregates is currently very challenging at the CCSDT level of theory even with the smaller aug-cc-pVDZ basis set.…”
Section: Electron Correlation and Basis Set Effectsmentioning
confidence: 79%
“…The performance of DFT have been rigorously investigated for the polarizabilities of large water clusters. 8 It was found that the accuracy of post-Hartree-Fock levels of theory was not sufficiently higher than that of DFT to justify the increased computational costs. In this work, we aim at extend this analysis to amino acid aggregates, through a careful estimation of the cost/benefits and the marginal utility of extending the level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the calculations in this work were performed using the modest-size cc-pVDZ basis-set. Even though augmentation with diffuse functions is highly desirable to accurately estimate electric moments and polarizabilities of molecules in an infinitely diluted gas, these functions are less relevant for estimating properties in aggregates or crystals, due to the existence of a "basis-set superposition" effect that takes place among basis-sets of vicinal groups or molecules in aggregation, see for example [14]. Otero et al [15] criticized the use of Equation (1) partitioned into their atomic contributions, without guaranteeing that the corresponding atomic basins are kept constant in the process.…”
Section: Distributed Atomic and Functional-group Polarizabilitiesmentioning
confidence: 99%
“…Incorporation of a fraction of Hartree-Fock exchange in to the GGAs is an established approach for alleviating this problem. In particular, a popular PBE-based hybrid functional, PBE0 [27], widens the HOMO-LUMO gap of the isolated water molecule by ∼40% and provides more accurate polarizabilities and interaction energies within a variety of water clusters [28][29][30]. When applied to ice, the lattice energies obtained with PBE0 (Table I) are indeed improved over PBE, however, the energy difference between ice Ih and ice VIII is still about four times larger than the experimental value.…”
mentioning
confidence: 96%